FOXL2 and DMRT1L Are Yin and Yang Genes for Determining Timing of Sex Differentiation in the Bivalve Mollusk Patinopecten yessoensis - Li, Ruojiao; Zhang, Lingling; Li, Wanru; Zhang, Yang; Li, Yangping; Zhang, Meiwei; Zhao, Liang; Hu, Xiaoli; Wang, Shi; Bao, Zhenmin (Frontiers in Physiology, 2018)
Sex determination and differentiation have long been a research hotspot in metazoans. However, little is known about when and how sex differentiation occurs in most mollusks. In this study, we conducted a combined morphological and molecular study on sex differentiation in the Yesso scallop Patinopecten yessoensis. Histological examination on gonads from 5- to 13-month-old juveniles revealed that the morphological sex differentiation occurred at 10 months of age. To determine the onset of molecular sex differentiation, molecular markers were screened for early identification of sex. The gonadal expression profiles of eight candidate genes for sex determination or differentiation showed that only two genes displayed sexually dimorphic expression, with FOXL2 being abundant in ovaries and DMRT1L in testes. In situ hybridization revealed that both of them were detected in germ cells and follicle cells. We therefore developed LOG10(DMRT1L/FOXL2) for scallop sex identification and confirmed its feasibility in differentiated individuals. By tracing its changes in 5- to 13-month-old juveniles, molecular sex differentiation time was determined: some scallops differentiate early in September when they are 7 months old, and some do late in December when they are 10 months old. Two kinds of coexpression patterns were found between FOXL2 and DMRT1L: expected antagonism after differentiation and unexpected coordination before differentiation. Our results revealed that scallop sex differentiation co-occurs with the formation of follicles, and molecular sex differentiation is established prior to morphological sex differentiation. Our study will assist in a better understanding of the molecular mechanism underlying bivalve sex differentiation.